2010
DOI: 10.1074/jbc.m110.145185
|View full text |Cite
|
Sign up to set email alerts
|

Co-assembly of Kv4 α Subunits with K+ Channel-interacting Protein 2 Stabilizes Protein Expression and Promotes Surface Retention of Channel Complexes*

Abstract: Members of the KMembers of the Shal subfamily of voltage-gated K ϩ (Kv) channel pore-forming (␣) subunits encode rapidly activating and inactivating Kv channels that also recover rapidly from inactivation and are important in the generation of I A channels in neurons (1-4) and I to channels in cardiac myocytes (5, 6). Accumulating evidence suggests that functional Kv4 channels reflect the assembly of Kv4 ␣ subunits with one or more Kv channel accessory subunits and other regulatory proteins that influence chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
46
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(60 citation statements)
references
References 35 publications
11
46
1
Order By: Relevance
“…Several previous studies also suggest a critical role for the KChIPs in the generation of native Kv4-encoded channels and that Kv4-KChIP protein-protein interactions are required for the stability of both proteins (25,(35)(36)(37)(38)(39). Interestingly, a similar stabilizing effect has been described for the Shaker channel accessory subunit, Sleepless, in Drosophila (40).…”
mentioning
confidence: 55%
“…Several previous studies also suggest a critical role for the KChIPs in the generation of native Kv4-encoded channels and that Kv4-KChIP protein-protein interactions are required for the stability of both proteins (25,(35)(36)(37)(38)(39). Interestingly, a similar stabilizing effect has been described for the Shaker channel accessory subunit, Sleepless, in Drosophila (40).…”
mentioning
confidence: 55%
“…According to previous studies, the single channel conductance of Kv4 (ϳ5 picosiemens) was not affected by the co-expression of KChIP proteins (38,42). It was reported that KChIP binding to the N terminus of Kv4.2 promotes the trafficking of Kv4.2 to the plasma membrane from the endoplasmic reticulum or Golgi (22,23,39,43). Consistent with these findings, we also observed that the surface expression of Kv4.2 increased in accordance with the increase in co-expressed KChIP4 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Does the Stoichiometry of the Kv4.2⅐KChIP4 Complex Change on the Cell Membrane?-As mentioned above, KChIP is known to promote the translocation of Kv4.2 from the endoplasmic reticulum or Golgi to the cell surface (22,23,39,43). Thus, KChIP binds to Kv4.2 in the endoplasmic reticulum and is required for the transport of the complex to the cell surface.…”
Section: Discussionmentioning
confidence: 99%
“…Electrophysiological studies support the idea that both the N and C termini of Kv4 channels interact to regulate the inactivation kinetics (40,42), opening the possibility that such interactions are modulated by binding of KChIPs at the N terminus (34,38). It is also proposed that the N terminus functions as a membrane transport control, which in the absence of KChIPs anchors Kv4 channels near the perinuclear region of the cell (43,44). The association of KChIPs at the T1 domain of Kv4 results in translocation to the membrane and a concomitant increase in total K ϩ current.…”
Section: Discussionmentioning
confidence: 99%